2008
DOI: 10.1890/07-0710.1
|View full text |Cite
|
Sign up to set email alerts
|

Transporting Juvenile Salmonids Around Dams Impairs Adult Migration

Abstract: Mitigation and ecosystem-restoration efforts may have unintended consequences on both target and nontarget populations. Important effects can be displaced in space and time, making them difficult to detect without monitoring at appropriate scales. Here, we examined the effects of a mitigation program for juvenile salmonids on subsequent adult migration behaviors and survival. Juvenile chinook salmon (Oncorhynchus tshawytscha) and steelhead (O. mykiss) were collected and uniquely tagged with passive integrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 69 publications
1
61
2
Order By: Relevance
“…The general lack of delayed effects may have been because fish were not spatially aggregated after exiting refugia or because there was no clear threshold temperature for refugia exit timing. The single statistically significant delayed effect was that Snake River fish that were barged as juveniles had lower upstream survival, consistent with a broader pattern of reduced homing and increased migration mortality for transported fish (Keefer et al 2008b).…”
Section: Mortality Trade-offsmentioning
confidence: 65%
See 1 more Smart Citation
“…The general lack of delayed effects may have been because fish were not spatially aggregated after exiting refugia or because there was no clear threshold temperature for refugia exit timing. The single statistically significant delayed effect was that Snake River fish that were barged as juveniles had lower upstream survival, consistent with a broader pattern of reduced homing and increased migration mortality for transported fish (Keefer et al 2008b).…”
Section: Mortality Trade-offsmentioning
confidence: 65%
“…Some steelhead were almost certainly last recorded in nonnatal locations (i.e., they were ''strays'') and their population assignment was therefore incorrect. In previous analyses, Snake River steelhead were most likely to stray into the Deschutes and John Day rivers (Keefer et al 2008b), and this should be considered in the interpretation of results. For example, some fish assigned to the Deschutes and John Day rivers were likely from upriver populations, adding a small bias of unknown direction to thermoregulatory estimates for these stocks.…”
Section: Stock and Fate Assignmentsmentioning
confidence: 96%
“…We also considered interbasin strays to be successful migrants regardless of their ultimate destination. Permanent strays were those last detected inside non-natal tributaries downstream from Lower Granite Dam either at fixed-site aerial radiotelemetry antennas or while mobile tracking (see Keefer et al 2008). Mortalities included salmon and steelhead whose final radiotelemetry records were in reservoirs or at dams.…”
Section: Pinniped-caused Injuries and Survivalmentioning
confidence: 99%
“…Haeseker et al (2012) provided further evidence for hydro-DM by demonstrating that freshwater and ocean survival is correlated, and concluded that increased spill and decreased transit time in the hydrosystem improved survival in both environments. Anderson et al (2011) reviewed the numerous potential causes of transport-DM, including physiological or behavioural stress associated with dam bypass facilities (Budy et al 2002), co-transportation with steelhead salmon Oncorhynchus mykiss (Congleton et al 2000), increased disease transmission (Van Gaest et al 2011), smaller body size and earlier ocean entry of transported smolts (Muir et al 2006) and impaired adult homing abilities (Keefer et al 2008). Although there is no consensus on how delayed mortality of transported spring Chinook salmon occurs, timing of transport appears to be important (Muir et al 2006, Smith et al 2013.…”
Section: Introductionmentioning
confidence: 99%